BENEFITS OF INTRADIALYTIC EXERCISE TO INCREASE MUSCLE STRENGTH, PREVENT MUSCLE MASS LOSS ON CHRONIC RENAL FAILURE PATIENTS ON HEMODIALYSIS: REVIEW - Desak Wayan (JURNAL KEPERAWATAN CIKINI, 2021)
Introduction:Prolonged exposure to hemodialysis treatments has a catabolic effect on muscles also compounding this expedited muscle loss associated decrease quality of life. The aim of this study is to investigate the benefits of intradialytic exercise programs, specifically on increase muscle strength and physical function. Methods: search in PubMed, ProQuest, and MEDLINE (EBSCO) about intervention intradialytic exercise program of CRF patients impairment muscle strength. Studies included intradialytic exercise program randomized controlled trials study design. Result: Most studies included in this review focused on intradialytic exercise program. These intervention program seems to increase muscle strength and improved physical function, and less decline in muscle cramp. Conclusion: Patients with CRF on hemodialysis need to do intradialytic exercise program. In addition, standardization of intradialytic exercise program, outcome and evaluation for patients with CRF on hemodialysis especially on muscle strength and muscle cramp, muscle mass, physically function is needed for further studies.